Stoner : a novel - Williams, John, 1922-1994 (Vintage classics (London, England), 2012)
The son of a midwestern farmer, William Stoner comes to the University of Missouri in 1910 to study agriculture. Stoner tells of love and conflict, passion and responsibility against the backdrop of academic life in the early 20th century.